DEVELOPMENT OF CONSTRUCTIONAL STEELS GRADES FOR AUTOMOTIVE INDUSTRY AT JSC BMZ - Ju. N. Dokudovskiy; P. K. Gribovskiy; V. A. Politov (Литьë и металлургия, 2012)
The program, directed on development of the technology of structural steels production for automotive industry, is developed at JSC «BMZ» in frame of implementation of innovative technologies on development of automobile steel grades.